The Effect of Using Vocabulary Self-Collection Strategy on Students’ Reading Comprehension and Their Motivation - Zulfirman Zani; jonri kasdi (Indonesian Journal of Integrated English Language Teaching, 2016)
The main aim of this study was to find out the effect of using vocabulary self-collection strategy on students’ reading comprehension and their motivation at Language Development Center of UIN SuskaRiau. It was a quasi-experimental research which was carried out in Comparison Group Pre-test/Post-test Design. The sample of this research was students of the Language Development Center who took English course at Level 2. They were divided into two groups, namelyan experimental class (PB 15) and acontrol class (PB 16) with a total of 58 students. The data were collected by using a reading comprehension test and a questionnaire. Vocabulary self-collection strategy was applied as treatment. The result of this research shows that there was a significant effect ofthe treatment on the students’ reading comprehension in the experimental group. The t-test result was 4.259;and its df was 56, by comparing number of significance. If probability is >0.05, the null hypothesis (H0) is rejected. If probability is <0.05, the alternative hypothesis (Ha) is accepted. Because of the significance was 0.000 < 0.05, Ha was accepted; and consequently H0 was rejected. There was also a significant effect of the treatment on the students’ motivation inthe experimental group. The t-test result was 8.431;and its df was 56, by comparing number of significance. Because of the significance was 0.000 < 0.05, thus, Hawas accepted andH0 was rejected.